EVALUATION OF DNA EXTRACTION METHOD FROM FORMALIN PRESERVED SKIN SAMPLES OF PANTHERA PARDUS FOR MOLECULAR GENETIC ASSESSMENT - S. S. Bibi; A. Rehman; R. A. Minhas; S. Janjua (Journal of Animal and Plant Sciences, 2015)
Five different protocols, viz. Andleeb et al. (2012), Shrivastava et al. (2012), Phenol chloroform DNA extraction method, Roboscreen Kit method and Phenol chloroform triton method, were tested for DNA extraction from skin samples of Leopard (Panthera pardus) preserved in formalin over a period of two to five months. Among these procedures, the Phenol chloroform triton method was proved to be the most efficient protocol with 83% extraction rate and revealed 100% amplification of FCA026 and FCA043 loci. Keeping in views the extraction and amplification efficiency, Phenol chloroform triton method is recommended for molecular studies of formalin preserved skin samples of Panthera pardus.
Keywords: Skin Tissue Samples; DNA Extraction; Polymerase Chain Reaction